(3QSGdI aj GdCcSjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hbdJ Pdc ai aUhd GdaUd GdChd ai GdCeQ Gdcdi dgPg GdUfGYI s
(3BNQgG (B:s
(3heKGd GdcdS GdCQV hGdCHjV fLRJ GdQSGdI hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3WHbGJ GdCWHGA L (B2 (3U (B2s
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdcjejGA h GdWHjYjGJs